Aspects of de Sitter Vacua in Theoretical Cosmology - Liu, Yang (2025)
The work presented in this thesis is based on research conducted at the Particle Theory Group, School of Physics and Astronomy, University of Nottingham, United Kingdom. In this thesis we explore de Sitter vacua in theoretical cosmology. The thesis has two parts. In Part I we consider different stringinspired models which are related to the cosmological constant problem. In Part II we study the de Sitter vacua solutions in one string cosmology model, namely, O(d, d) invariant cosmology.